Dental Caries in Relation to Sugar Consumption Among Children, A Study from Public Sector Hospital of Southern Punjab, Pakistan - Simra Ali Mughal, Seemab Rehman, Kashaf Rana, Jaffar Hussain Bukhari, Ahmed Ali Qureshi, Rabia Majeed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this study was to investigate the prevalence of dental caries among the children presenting in a public dental hospital of South Punjab, Pakistan, as dental caries has been one of the most prevalent diseases among children all around the world. Different factors play a significant role in caries incidence, sugar intake being the most important one. Caries not only leads to dental pain, but also effects a child’s body functions, productivity and growth. This study evaluates the factors responsible for caries incidence among children. Methodology: This cross-sectional study was conducted at the Nishtar Institute of Dentistry, Multan, Pakistan from August, 2022 to December, 2022. Data were collected on a specifically designed questionnaire. A total of 370 participants of age range between 3 to 12 years were chosen for this study. Consent from their parents was taken. The data were analyzed by using SPSS 22 and applying Eta-square test and Pearson’s correlation. Results: Gender had no significant effect on DMFT score with p-value of 0.3. Type and frequency of sugar intake had a significant effect with p-value of 0.00 for both. Age and DMFT were found to have a negative linear relationship. Conclusion: Increased refined sugar intake was the leading cause of dental caries among children of local population of South Punjab. Keywords: Dental caries, Caries, Children, Sugar Intake